Pemanfaatan Media KoCar Sebagai Pilihan untuk Meningkatkan Hasil Belajar Siswa - Nawangwulan Cahyaristi; Puguh W. Prasetyo; Sugiyem Sugiyem (UNION : Jurnal Ilmiah Pendidikan Matematika, 2022)
This exploration begins from the low math learning results of class VIII G understudies at SMP Negeri 1 Nubatukan. This is tracked down in the aftereffects of re-obtainment in class. Taking into account the consequences of the exploration on the Cartesian directions material, it was acquired information that there were still understudies who had not finished as per the Base Fulfillment Rules (KKM), which was 60. Of the 27 understudies, just 14 understudies or 51.85% passed. The inspiration driving this exploration is to settle on the utilization of KoCar media in the further advancement of understudy learning results on the Cartesian Directions material. The sort of exploration applied is Study hall Activity Exploration (Vehicle) which is brought out through 2 (two) cycles with each cycle comprising of 4 (four) stages, specifically the preparation, execution, perception, and assessment stages. The outcomes showed an expansion in understudies' arithmetic learning results in the wake of learning with KoCar media was applied, which was set apart by an expansion in scores from 53.22 to 82.41 in cycle II. Furthermore, understudies' activities have created during the educating and educational experience in the study hall. In light of the consequences of the execution of this learning, one might say that the utilization of KoCar media can additionally further develop the learning results of class VIII G understudies on the Cartesian Directions material.